Suppression of allelic recombination and aneuploidy by cohesin is independent of Chk1 in Saccharomyces cerevisiae. - Shay Covo; Eric Chiou; Dmitry A Gordenin; Michael A Resnick (PLoS ONE)
Sister chromatid cohesion (SCC), which is established during DNA replication, ensures genome stability. Establishment of SCC is inhibited in G2. However, this inhibition is relived and SCC is established as a response to DNA damage, a process known as Damage Induced Cohesion (DIC). In yeast, Chk1, which is a kinase that functions in DNA damage signal transduction, is considered an activator of SCC through DIC. Nonetheless, here we show that, unlike SCC mutations, loss of CHK1 did not increase spontaneous or damage-induced allelic recombination or aneuploidy. We suggest that Chk1 has a redundant role in the control of DIC or that DIC is redundant for maintaining genome stability.